Impact of Microfinance on Microbusinesses: Case of Haryana, India - Mor, Nishant; Mor, Surender (International Journal of Psychosocial Rehabilitation, 2020)
The paper examines the impact of microfinance on the performance of microbusinesses 349 micro-enterprises in the Haryana state of India, by considering profit as a proxy for the performance of the sampled micro-businesses. The findings suggest a significant difference among the various level of microfinancing and their effectiveness in impacting the profitability of the designated business. The results suggest that the performance of micro-businesses availing microfinance in the range of Rs 30,000-50,000, is much better than those with a low level or high levels of microfinance. The verdict advised that for augmenting the profitability or performance of the microenterprises in Haryana; the level of microfinance needs to be maintained at a middle level, i.e., microbusinesses cannot realize their full potential (highest profit) either with a shallow level or too much finance. The study advocates that the level of microfinancing (investment) need to be raised for enhancing the profitability as well as perforamce and long-run survival of the micro-businesses operational in Haryana.